KAJIAN KEBIJAKAN PPN ATAS BAHAN BAKAR MINYAK UNTUK KAPAL TUJUAN INTERNASIONAL (STUDY ON VALUE ADDED TAX POLICY ON INTERNASIONAL BUNKER FUEL) - Widia, I Nyoman (Jurnal Kajian Ekonomi dan Keuangan, 2010)
This study focus on value added tax policy on international bunker fuel. Current regulation in Indonesia describes that government has imposed value added tax 10% on bunker fuel. Qualitative Approach was used in this study. As a result, imposing value added tax on bunker fuel against the international best practice. According to Value Added Tax Law, Government of Indonesia may give an incentive on bunker fuel.